2022
DOI: 10.1007/s10943-022-01709-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Prayer-Based Interventions Effective Pain Management Options? A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: This review examined the effects of private and communal participatory prayer on pain. Nine databases were searched. Six randomized controlled trials were included. For private prayer, medium to large effects emerged for 67% to 69% of betweengroup comparisons; participants in the prayer condition reported lower pain intensity (0.59 < d < 26.17; 4 studies) and higher pain tolerance (0.70 < d < 1.05; 1 study). Preto post-intervention comparisons yielded medium to large effects (0.76 < d < 1.67; 2 studies); pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…A meta-analysis of 19 studies comparing Transcendental Meditation (TM) to non-religious/spiritual forms of meditation showed that TM had greater enhancements in terms of reducing anxiety and drug use as well as increasing positive mental health on measures of self-actualization than non-religious/spiritual practices [ 1 ]. A recent meta-analysis of prayer-based interventions suggested that participatory prayer as an adjunct to standard pain treatment may further reduce pain intensity among those with pain conditions or undergoing painful procedures [ 31 ]. Christian prayer practices have also been investigated, though to a lesser extent (see [ 39 , 71 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 19 studies comparing Transcendental Meditation (TM) to non-religious/spiritual forms of meditation showed that TM had greater enhancements in terms of reducing anxiety and drug use as well as increasing positive mental health on measures of self-actualization than non-religious/spiritual practices [ 1 ]. A recent meta-analysis of prayer-based interventions suggested that participatory prayer as an adjunct to standard pain treatment may further reduce pain intensity among those with pain conditions or undergoing painful procedures [ 31 ]. Christian prayer practices have also been investigated, though to a lesser extent (see [ 39 , 71 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Centering Prayer has been investigated in an uncontrolled study among parishioners and was found to reduce levels of stress and anxiety from baseline to post-intervention [ 19 ]. Another uncontrolled pilot study among women diagnosed with cancer showed improvements in well-being and reductions in anxiety after engaging with Centering Prayer [ 31 ]. These initial studies provide promising data to justify a better powered and more rigorously designed study on Centering Prayer.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 17 Furthermore, a recent meta-analysis demonstrated that private prayer is associated with lower pain intensity and greater pain tolerance. 18 Notably, distant intercessory prayer and group-based prayer studies have fallen into disfavor because of methodological challenges that undermine the ability to draw conclusions from the data. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Praying subscale of the Coping Strategies Questionnaire–Revised (CSQ-R 23 ) is the only validated measure of prayer in response to pain, and it assesses only passive prayer. Because prayer in all its expressions can have a different, complex association with pain, 10 , 18 it is necessary to develop a more comprehensive measure of prayer for pain to better understand the relationship between prayer and pain. Specifically, this measure should include an active style of prayer, as well as neutral prayer, which will capture those who might not pray to God, might be agnostic, or might meditate, using spiritual as opposed to religious prayer to cope with their pain.…”
Section: Introductionmentioning
confidence: 99%